(untitled) (Research, Society and Development, 2020)
Objective: To analyze the influence of sleep on the quality of life (QoL) and academic performance of medical students. Methodology: Cross-sectional, quantitative, observational, descriptive and individual study, carried out with 303 students from the 1st to the 8th semester of the Medicine course at a public university in the interior of Ceará. The research was carried out based on an adaptation of the Pittsburgh Sleep Quality Index to the Brazilian reality. The data was transferred to an Excel spreadsheet. Results and Discussion: 58% of participants sleep less than 7 hours a day, a number lower than recommended in the literature. 84.1% of these reported waking up in the middle of the night or earlier than expected in the morning, disturbing the sleep’s duration. Among factors studied that are harmful to sleep were coughing, snoring, inadequate room temperature, nightmares, pain and anxiety related to personal and academic life. 75.3% reported difficulty staying awake during the day to carry out daily activities, and 88.5% said they had problems maintaining their spirits to carry out daily activities. Conclusion: Poor multifactorial sleep quality is perceived, strongly associated with a loss in QoL and academic performance, demonstrating the need for concern with sleep hygiene.